Experience and outcomes of micrografting for major paediatric burns. Issue 5 (August 2017) - Rode, H.; Martinez, R.; Potgieter, D.; Adams, S.; Rogers, A.D.
Abstract: Background: The deficit of donor sites in major burns over 50% of the total body surface area has necessitated the application of methods besides traditional meshed autografting to achieve definitive skin cover. The Meek micrografting technique was introduced at this hospital in 2011, especially in the absence of a reliable source of deceased donor allograft skin. The purpose of this study was to evaluate this strategy with reference to its technical execution, efficacy and indications in the context of major paediatric burn surgery. Methods: A cohort study was performed of all paediatric patients with major burn who underwent Meek micrografting at a dedicated paediatric burn centre in a developing country over a five year period. Demographics, details of their burns, operative management and clinical course and outcomes were collected from patient records and operative notes and analysed. Results: Thirty-five patients were managed using the micrografting technique during the study period. The mean patient age was 4.1 years (range 3 months–11 years) and their mean total body surface area (TBSA) burn was 49.7% (range 15–86%). Eleven patients sustained inhalation injuries and five developed a re-feeding syndrome on account of delayed referral. The mean abbreviated burn severity index (ABSI) was 8.5 (range 2–13). The hospital length of stay in the 27 survivors was a mean of 75.5 days, equating to 1.4 days per percentage burn. Eight patients died during the course of treatment, with a mean TBSA burn of 67.75% (range 38–86%). Graft take one month after surgery was documented to be more than 90% in 24 patients, of whom 3 subsequently died. Eleven patients had less than 90% graft take at this time, of whom 5 died. Conclusion: There is a considerable 'learning curve' associated with this technique. In order to achieve success one must ensure a completely viable, non-infected bed, obtained by tangential or fascial excision, followed by allografting as temporary coverage and to 'test the wound bed' for definitive coverage. Infection resulted in the majority of autograft loss in this series, and in addition to risk factors like burn size and inhalation injury, accounted for many of the deaths in this series. Meek micrografting offers high expansion ratios, thereby facilitating durable wound cover in the presence of limited donor sites. It is unlikely that a lethal dose, 50% (LD50 ) of almost 70% TBSA would have been possible in this context without the regular application of this technique. This study advocates for the widespread availability of Meek micrografting and deceased donor allograft skin in developing countries.